THE USE OF COOPERATIVE LEARNING TO IMPROVE STUDENTS' ABILITY IN READING COMPREHENSION IN MTS NURUL BAROKAH 2017 - Ai Munawaroh (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2017)
Abstract This paper reports a study of using cooperative learning to improve Students’ ability in English reading comprehension of recount text. Because reading still becomes one of the problems which students face at school including Secondary School. Cooperative learning is one of the several methods which gives much opportunity for students in group with various abilities for comprehending of recount text. The aims of this study are to investigate use of cooperative learning and to find out the students' response of using cooperative learning for improving students' ability in English reading comprehension. This study applied mix method design by using triangulation by one group pre-test and post-test design. The quantitative data was obtained by students’ score in English reading pre-test and post-test of recount text. Meanwhile, the qualitative data were obtained from classroom observation and interview. The study was conducted at one of the Islamic Junior High Schools in Cianjur which involved 24 students in eighth grade. The findings showed the hypothesis testing proved that tcount ≥ ttable 14,29≥1.714. Therefore, the null hypothesis was rejected. It meant, the use of cooperative learning could improve students’ ability in English reading comprehension. Another finding also showed students’ responses were positive. They responded that cooperative learning is more enjoyable. Furthermore, it helps them in understanding recount text and also it could be applied as one of the teaching reading to be implemented in Secondary School. Key words: Reading, Reading Comprehension, Cooperative Learning and Recount Text